Prospects for the sectoral transformation of the rural economy in Tanzania: A review of the evidence - Benson, Todd; Randriamamonjy, Josee; Fang, Peixun; Nyange, David; Thurlow, James; Diao, Xinshen (Michigan State University, 2017)
To guide economy-wide modeling efforts to identify specific public investments under Tanzania’s second Agricultural Sector Development Programme (ASDP II), this report provides an analysis of the performance of the rural economy of mainland Tanzania over the period 2008 through 2015, with a focus on the agriculture sector. More broadly, we seek to assess the nature and extent of any structural transformation in the rural economy by understanding trends in various components of it. The insights gained will then be used in the economy-wide modeling work to propose portfolios of public investments to foster both agricultural development in the short term—in alignment with the ASDP-II—and, in the longer-term, a sectoral transformation of the rural economy in which far fewer households rely solely on agriculture for their livelihoods.